Import of laugher in police-suspect interaction in Ibadan, Nigeria: a multimodal analysis - Ajayi, Temitope M. (African journal of criminology and justice studies, 2020)
Studies on police-suspect interaction (PSI) have engaged the textual peculiarities of PSI. Scholarly works on the non-verbal mode of communication in PSI are very scanty. Dearth of studies in this regard has prevented an investigation of the significance of the non-verbal mode as a communicative tool in PSI. This study examines the resourcefulness of laughter as a non-verbal mode in PSI with a view to uncovering the contextual roles of laughter in PSI. The study adopts Norris’ multimodal interaction analysis theory to investigate the motivations behind the deployment of laughter by investigating police officer (IPOs) and suspects during interrogation sessions. Data were collected at the Criminal Investigation Department, Iyaganku, Ibadan, Oyo State. Analysis of data reveals that, with particular attention to social context, IPOs and suspects engage laughter to build rapport, mitigate tension, modify verbal expressions and attitude, orchestrate deception, mock suspects, evade questions and maintain social order. The social actors’ recourse to laughter as a meaning making mode reveals how their identities are co-constructed in the interaction.